1983
DOI: 10.1172/jci111142
|View full text |Cite
|
Sign up to set email alerts
|

Nature and quantity of fuels consumed in patients with alcoholic cirrhosis.

Abstract: A B S T R A C T Although alcoholism is a leading cause of morbidity and mortality of middle-aged Americans, there are no data available pertaining to the consequences of Laennec's cirrhosis on total body energy requirements or mechanisms for maintaining fuel homeostasis in this patient population. Therefore, we simultaneously used the techniques of indirect calorimetry and tracer analyses of ["4C]palmitate to measure the nature and quantity of fuels oxidized by patients with biopsy-proven alcoholic cirrhosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
151
2
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(174 citation statements)
references
References 36 publications
(40 reference statements)
8
151
2
10
Order By: Relevance
“…Methodological variation, poor matching of control subjects, and referencing of data to body composition variables determined using unvalidated methods 61 limit the conclusions that can be drawn from other studies on REE in this patient population. [16][17][18][19][20][21][22] Nevertheless, the proportion of patients identified as hypo-and hypermetabolic in the present study are similar to those reported previously. 17,28,33,62 In our patients with cirrhosis, the Harris-Benedict, Schofield, Mifflin, and Owen formulae yielded mean predicted values for REE that significantly underestimated the mean measured value by 6%, 3%, 11%, and 7%, respectively, while the Cunningham formula significantly overestimated the mean measured value by 5%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Methodological variation, poor matching of control subjects, and referencing of data to body composition variables determined using unvalidated methods 61 limit the conclusions that can be drawn from other studies on REE in this patient population. [16][17][18][19][20][21][22] Nevertheless, the proportion of patients identified as hypo-and hypermetabolic in the present study are similar to those reported previously. 17,28,33,62 In our patients with cirrhosis, the Harris-Benedict, Schofield, Mifflin, and Owen formulae yielded mean predicted values for REE that significantly underestimated the mean measured value by 6%, 3%, 11%, and 7%, respectively, while the Cunningham formula significantly overestimated the mean measured value by 5%.…”
Section: Discussionsupporting
confidence: 91%
“…[12][13][14][15] However, there is no consensus in the data on energy expenditure, and thus energy requirements, in this patient population. [16][17][18][19][20][21][22] Plauth et al 23 recommended that energy requirements should be determined in patients with cirrhosis by measurement of their resting energy expenditure (REE) using indirect calorimetry. They suggest, but do not advocate, that if the facilities for measurement are not available, then energy expenditure could be estimated by use of the Harris-Benedict prediction formulae.…”
mentioning
confidence: 99%
“…Some studies have reported an increased resting metabolic rate in cirrhotic patients (6)(7)(8), while others have described a normal (9,10) or low rate (11). In part, this variation may be the result of different methods used for measuring and calculating energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…It is highly recommended to make the periods of starvation shorter, by dividing the daily energy intake in multiple meals during the day. In fact, it has been shown that after overnight fast, cirrhotic patients experience a metabolic state similar to that of healthy subjects after 3 days of fasting, 50 with an increased gluconeogenesis from amino acids and increased lipolysis. A late evening snack has been found to be beneficial in cirrhotic patients to compensate the overnight fasting period.…”
Section: Indications For Malnourished Patients Waiting For Liver Tranmentioning
confidence: 99%